Sporadic Right Lumbar Intraabdominal Desmoid Tumor: A Case Report - Zen, Ong Xin; Zin, Anani Aila Mat; Zakaria, Zaidi; Yahya, Maya Mazuwin; Wong, Michael Pak Kai (Journal of Coloproctology, 2025)
Sporadic intraabdominal desmoid tumor is a rare occurrence, comprising 0.03% of all neoplasms. It has an estimated incidence of 2 to 4 per million in the general population. Only 15% of all desmoid tumors are intraabdominal. Often, they are present with abdominal distension or bowel obstruction symptoms. Desmoid tumors are not readily differentiated from others through computed tomography (CT) scans. We are sharing a case of a young (34-year-old) patient who presented with tender palpable right lower quadrant mass. The CT scan shows a well-defined intraperitoneal mass over the right lumbar region. Limited right hemicolectomy was done. Histopathology shows features consistent with desmoid tumors. Surgical excision remains the mainstay of treatment, though various nonsurgical treatments have been described with promising results. Our case of sporadic intraabdominal desmoid tumor was managed with surgical resection.
Keywords: fibromatosis; aggressive; desmoid disease; colorectal neoplasms